Effects of Cu doping on the properties of NiO film fabricated using the sol–gel method based on the rapid pyrolysis process. (22nd July 2020) - Song, Mengsi; Liu, Chaoqian; Wang, Nan; Lun, Tingting; Zhai, Xiaona; Ge, Qing; Zhang, Xiaoyang; Wu, Sumei; Liu, Shimin; Wang, Hualin; Jiang, Weiwei; Ding, Wanyu
Abstract : The sol–gel method based on the rapid pyrolysis process was adopted to prepare Ni1− x Cu x O ( x = 0–0.1) films on glass substrates. The effects of Cu doping on the structural, morphological, electrical and optical properties of the films were characterised by X‐ray diffractometer, scanning electron microscope, Hall effect instrument and ultraviolet‐visible spectrophotometer, respectively. The NiO‐based films have a cubic rock salt structure and it was found that the film with x = 0.06 should have minimal residual stress. The transmittance and bandgap of the films decreased with increasing Cu‐doping concentration. In addition, the compactness of the films increased along with the increase of Cu‐doping concentration as a whole. The carrier concentration of the films was almost invariable, but the carrier mobility was determined by the competition between the effects of the morphology and the ionised impurity scattering. The resistivity of the films first decreases and then increases, and the minimum resistivity was 182.1 Ω cm at x = 0.06.